Reclamation (Utilization of the Sea) in the Qur'an and Hadith Perspective - M. Solahudin; Irwan Abdurrohman (Indonesian Journal of Islamic Studies, 2018)
It is necessary to explore the concept of full sea use according to the Qur'an and hadith, specifically the use of the sea in the form of reclamation. The method used in this study is the library research method. Judging from its purpose, this research is classified as an exploratory type of research, because it aims to explore the use of sea discourse from the Qur'an and hadith. Judging from the presentation of the data, this research is critical analytical and analytical. Because this study makes interpretation (mufassir) and various hadits as material in library research. The results of the study state that, first, in the process, the use of the sea in the perspective of the 'an, basically contains conservation values. with reclamation, which contains an element of "improvement on something that is broken", it can be ascertained that it has conservation value. If the opposite happens, it does not have conservation value, then reclamation carried out is contrary to the meaning of reclamation itself, and also contrary to the values ​​of the Qur'an. Second, the use of the sea perspective basically contains conservation values. Likewise, the nature of reclamation basically contains environmental conservation values ​​if the elements of the use of the beach or the sea do not contradict the values. Conversely, if the reclamation process is carried out against the values, then the reclamation does not have conservation value for the environment.